(untitled) (Journal of Partial Differential Equations, 1992)
In this paper, we obtain two results of weak solutions to variational inequalities of triangular form under controllable growth and a class of natural growth conditions, i.e. 1^&#176. L^p-estimate for the gradient; 2^&#176. C^1,&#946_loc(&#937, R^N) regularity.